2011
DOI: 10.1088/0031-9120/46/2/007
|View full text |Cite
|
Sign up to set email alerts
|

High speed and slow motion: the technology of modern high speed cameras

Abstract: The enormous progress in the fields of microsystem technology, microelectronics and computer science has led to the development of powerful high speed cameras. Recently a number of such cameras became available as low cost consumer products which can also be used for the teaching of physics. The technology of high speed cameras is discussed, facilitating an understanding of the problems and restrictions in using these cameras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 15 publications
1
46
0
Order By: Relevance
“…Previous research has demonstrated that there are a number of clear benefits associated with increased frame rates, including: the visibility of temporal aliasing artefacts being diminished [10,[21][22][23][24][25][26]; a reduction in perceptible motion blur [23][24][25][27][28][29]; increased realism, smoother motion, improved depth perception for both expert [30] and non-expert [31] viewers (especially when tracking using smooth pursuit eye movements); more realistic motion image quality (confirmed using EEG data) [32]; a reduction in viewer stress levels [33] (signified by a lower blinking frequency [34]); an improvement in speed and spatial discrimination, and reading ability [35]; and an increase in perceptual quality [18,36], at least up to 240 fps [29]. The use of higher frame rates also enhances the ability to capture and playback slow-motion videos [37].…”
Section: A Benefits Of Increased Frame Ratesmentioning
confidence: 99%
“…Previous research has demonstrated that there are a number of clear benefits associated with increased frame rates, including: the visibility of temporal aliasing artefacts being diminished [10,[21][22][23][24][25][26]; a reduction in perceptible motion blur [23][24][25][27][28][29]; increased realism, smoother motion, improved depth perception for both expert [30] and non-expert [31] viewers (especially when tracking using smooth pursuit eye movements); more realistic motion image quality (confirmed using EEG data) [32]; a reduction in viewer stress levels [33] (signified by a lower blinking frequency [34]); an improvement in speed and spatial discrimination, and reading ability [35]; and an increase in perceptual quality [18,36], at least up to 240 fps [29]. The use of higher frame rates also enhances the ability to capture and playback slow-motion videos [37].…”
Section: A Benefits Of Increased Frame Ratesmentioning
confidence: 99%
“…Myotid bats, and other low duty cycle bats, prevent selfdeafening by desensitizing their ears as they emit their very loud echolocation pulses [28]. The wing morphology [6], body size [6] and the general occurrence of M. tricolor over water bodies [11] suggests that this species may be a generalist that utilises more than one foraging strategy; i.e. trawling or gleaning and aerial hawking.…”
Section: Discussionmentioning
confidence: 99%
“…The low acquisition time is caused by the limited internal memory storage and the high recording frame rate of commercial cameras. Subsequent data transfer from the internal camera memory to the external computer is performed at a much lower speed [8]. By removing on-camera memory buffers on our smart camera, the duration of the acquisition is prolonged and limited only by the size of the main memory (RAM) of the recording computer.…”
Section: Introductionmentioning
confidence: 99%